Infant attention to rhythmic audiovisual synchrony is modulated by stimulus properties - Cirelli, Laura K.; Talukder, Labeeb S.; Kragness, Haley E. (Frontiers in Psychology, 2024)
Musical interactions are a common and multimodal part of an infant's daily experiences. Infants hear their parents sing while watching their lips move and see their older siblings dance along to music playing over the radio. Here, we explore whether 8-to 12-month-old infants associate musical rhythms that they hear with synchronous visual displays by tracking their dynamic visual attention to matched and mismatched displays. Visual attention was measured using eye-tracking while they attended a screen displaying two videos of a tapping finger tapping at different speeds presented side by side, while exposed to an auditory rhythm (high or low pitch) synchronized with one of the two videos. Infants attended more overall in low compared to high pitch trials, but did not display a preference for attending to the synchronous over the asynchronous hand within trials. Exploratory evidence, however, suggests that tempo, pitch, and rhythmic complexity interactively engaged infants' visual attention to a tapping hand, especially when that hand aligned with the auditory stimulus. For example, when the rhythm was complex and the auditory stimulus was low in pitch, infants' attended the fast hand more when it aligned with the auditory stream than on misaligned trials. These results suggest that audiovisual integration in rhythmic non-speech contexts is influenced by stimulus properties.